Exterior of the garbhariha of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) of the Bhandasar Temple is pancharatha (consisting of five projections) in plan. The central projection is a broad opening on three sides, that leads into the garbhagriha. The subsidiary projections have sculptures on the jangha (wall). All the plinth and wall portions of the temple must have been originally made out of stone which was later painted. Many of the ornaments that the sculptures are shown wearing are mostly done in paint on the original stone carving.